Individualization Of Primary Class Educational Processes Based on Digital Technologies - Boriyeva Shakhnoza Inat Qizi (Periodica Journal, 2024)
This article discusses changes in the education system, effective tools in this process, the introduction of various forms of individualization of the education system based on digital technologies, and the convenience of using these technologies.
Keywords: Education; initial; quality; digitization